Seasonal Variation in Fat Quality and Conjugated Linoleic Acid Content of Dairy Products from the Tropics: Evidence of Potential Impact on Human Health - Juliana Côrtes Nunes; Monalisa Nilza Lole Ramalho da Silva; Daniel Perrone; Alexandre Guedes Torres (Foods, 2017)
Seasonal variation in conjugated linoleic acid (CLA) content and atherogenicity index (AI) of retail dairy products (whole milk, butter, and prato, a soft yellow cheese) from Brazil was investigated. CLA content of dairy products ranged from 0.55 to 1.53 g CLA/100 g fatty acids and was on average 25% higher during the rainy season compared to the dry season. Dairy products from the rainy season also had lower AI levels, indicating a lower risk of causing cardiovascular disease in consumers. This seasonality led to estimated seasonal variations of milk fat quality consumed by the population of southeastern Brazil, meaning 15% and 19% variation in daily intake of CLA and AI values, respectively. Dietary consumption of CLA (g/day) was greater in the rainy season, despite higher intake of dairy products during the dry season. We show that dairy products produced during the rainy season in Brazil are expected to be more beneficial to human health than are those produced during the dry season.